The impact of war on people with type 2 diabetes in Ukraine: a survey studyResearch in context - Oksana Sulaieva; Viktoriia Yerokhovych; Sergii Zemskov; Iuliia Komisarenko; Vitalii Gurianov; Volodymyr Pankiv; Oleksandr Tovkai; Tetyana Yuzvenko; Violetta Yuzvenko; Andrii Tovkai; Zlatoslava Shaienko; Tetyana Falalyeyeva; et al. (EClinicalMedicine)
Summary: Background: Although the number of studies reporting war-induced effects on the health of the Ukrainian population has been growing, there are still little data on assessing patients with type 2 diabetes (T2D) during the war. This study aimed to evaluate the impact of war on T2D patients’ health to define key risk factors promoting disease progression. Methods: A survey covering various aspects of T2D patients’ experience and glycemic control data was conducted from June 2022 to February 2024. Overall, 1193 patients from all regions of Ukraine were enrolled in the study. According to the difference between the initial and current levels of HbA1c, all the respondents were subdivided into two categories: progressors (with HbA1c levels greater than 5% of the initial value) and stable (patients with stable HbA1c levels). Next, the impact of intrinsic and war-related factors on T2D progression was assessed via logistic regression analysis and machine learning tools. Findings: Two years of war experience was associated with significant increase in the median HbA1c from 7.8% (7.0–8.93) to 8.4% (7.4–9.9; p < 0.001), with the highest value occurring in eastern and northern Ukraine. HbA1c levels demonstrated a time-dependent pattern of growth, reflecting the cumulative effect of war-related factors on T2D patients’ health. Witnesses of armed attacks and occupation aggravated the T2D course. Experience with military actions (p = 0.002), occupation (p = 0.001), internal displacement (p = 0.018) and family member injury or death (p = 0.031) increased HbA1c. In addition, lack of regular glucose monitoring (p < 0.001), consultation by endocrinologists (p < 0.001), diet inconsistency (p = 0.017) and scarcity of physical activity (p = 0.047) affected the HbA1c parameters. Interpretation: This study demonstrated a dramatic cumulative effect of the war on T2D patients’ health. Uncovered direct and indirect war-related risk factors can guide further adjustment of diabetic care in Ukraine to improve T2D patient support. Funding: National Research Foundation of Ukraine (grant number 2022.01/0089).